AUGMANTED REALITY PENGENALAN HEWAN PURBAKALA ANIMASI 3 DIMENSI DENGAN PATTERN RECOGNITION BERBASIS ANDROID - alvebi hopaliki; yupianti yupianti; juju jumadi (GATOTKACA Journal (Teknik Sipil, Informatika, Mesin dan Arsitektur), 2020)
Augmented Reality (AR) is a variation of the virtual environment or more often calledasAR technology users that can see the real world, with virtual objects added to the real world. So, users see virtual objects and real objects are in the sum place. Augmented reality requires streaming video with a camera that is used as a sowce of image input, then tracking and detecting markers. After the W is detected 30 model will appear of an item. This 3D model was mated mite software for 3D design, jbr example 3DS Max. Blender and others In this ancient animal Ieaming media using pattern recognition that can be interment! as taking raw data and based on data classification Then it can take the mutation problem how to design 30 objects with the Blender application to introduce d anc‘ient animals. purpose of this m is to build ancient animal leaning media in real time by using augmented reality technology.